Some hyperstability and stability results for the Cauchy and Jensen equations - Mohammad Bagher Moghimi; Abbas Najati (Journal of Inequalities and Applications, 2022)
Abstract In this paper we give some hyperstability and stability results for the Cauchy and Jensen functional equations on restricted domains. We provide a simple and short proof for Brzdȩk’s result concerning a hyperstability result for the Cauchy equation.